Pengaruh modul pembelajaran berbasis self regulated learning dengan menggunakan model inquiry learning terhadap hasil belajar siswa - Friti Chinta Talib (Universitas Muhammadiyah Mataram, 2026)
AbstractChanges in teaching and learning practices during and after the pandemic have highlighted the need for instructional materials that support independent learning, enhance student engagement, and foster critical thinking skills. However, physics instruction in schools is still largely dominated by conventional teaching methods, resulting in suboptimal student achievement, particularly in the topics of temperature and heat. Therefore, this study aimed to investigate the effect of a self-regulated learning (SRL)-based learning module integrated with the inquiry learning model on students’ learning outcomes. This study employed an experimental method using a pretest-posttest control group design. The research sample consisted of two classes, namely an experimental class and a control class, each comprising 10 students selected through cluster random sampling. The research instrument was a set of 12 validated essay questions. Data were analyzed using normality tests, homogeneity tests, hypothesis testing, and N-Gain analysis at a significance level of 0.05. The results of the hypothesis test revealed a significant effect of the inquiry-based learning model and the self-regulated learning module on students’ learning outcomes. The obtained t-value (4.974) at the 0.05 significance level was higher than the t-table value (2.024), indicating that H0 was rejected and H1 was accepted. The difference in learning outcomes between the experimental and control groups was also supported by the N-Gain scores, where the experimental class achieved a score of 0.50, higher than the control class score of 0.32. These findings indicate that learning using self-regulated learning modules is more effective than conventional teaching methods. Overall, the module had a significant effect on improving students’ understanding of temperature and heat concepts.Keywords: learning module; self-regulated learning; inquiry learning model; learning outcomes. AbstrakPerubahan praktik pembelajaran selama dan pascapandemi menuntut adanya bahan ajar yang mampu mendukung pembelajaran mandiri, meningkatkan keterlibatan siswa, serta mengembangkan kemampuan berpikir kritis. Namun, pembelajaran fisika di sekolah masih didominasi metode konvensional yang menyebabkan hasil belajar siswa pada materi suhu dan kalor belum optimal. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pengaruh modul pembelajaran berbasis self regulated learning (SRL) dengan menggunakan model inquiry learning terhadap hasil belajar siswa. Penelitian ini menggunakan metode eksperimen dengan desain pretest-posttest control group design. Sampel penelitian terdiri atas dua kelas, yaitu kelas eksperimen dan kelas kontrol yang masing-masing berjumlah 10 siswa dan dipilih menggunakan teknik cluster random sampling. Instrumen penelitian berupa tes esai sebanyak 12 soal yang telah divalidasi oleh ahli. Teknik analisis data menggunakan uji normalitas, uji homogenitas, uji hipotesis, dan uji N-Gain pada taraf signifikansi 0,05. Hasil uji hipotesis menunjukkan adanya pengaruh signifikan penggunaan model pertanyaan dan modul pembelajaran self-regulated terhadap hasil belajar siswa. Nilai thitung (4,974) pada taraf signifikansi 0,05 lebih besar dibandingkan ttabel (2,024), sehingga H0 ditolak dan H1 diterima. Perbedaan hasil belajar antara kelas eksperimen dan kontrol juga didukung oleh nilai N-Gain, di mana kelas eksperimen memperoleh skor 0,5, lebih tinggi dari skor 0,32 pada kelas kontrol. Temuan ini menegaskan bahwa pembelajaran berbasis modul self-regulated lebih efektif daripada metode konvensional. Secara keseluruhan, modul tersebut berpengaruh signifikan dalam meningkatkan pemahaman siswa mengenai materi suhu dan kalor.Kata kunci: modul pembelajaran; self regulated learning; model inquiry learning; hasil belajar.